IMPLEMENTASI METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 018 MARSAWA - Hasni Warlis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Mathematics is one of the branches of science that has the most connection with other branches of science which function to advance students' thinking scientifically and construct new knowledge gained by students. Mathematics functions to develop the ability to communicate using numbers and symbols and sharpness of reasoning that can help clarify and solve problems in everyday life. The purpose of this study was to increase the mathematics learning outcomes of class I students of 018 Marsawa State Elementary School. This research is a classroom action research consisting of two cycles, namely cycle I and cycle II. Based on observations, researchers found student learning outcomes were still relatively low. Students who complete mathematics learning or who achieve minimum completeness criteria are only 10 students or (45.4%) while students who do not complete or have not reached the minimum completeness criteria are 12 students or (54.5%). With a grade average of 56. To overcome this learning problem researchers used a demonstration learning model. The results of the study showed an increase in learning outcomes per cycle, when viewed from the initial data, the classical average value was 56 with a moderate category. After carrying out the first cycle the average value became 64.6 moderate categories and in the second cycle increased to 91.6 very good categories. Based on the results of the study researchers can conclude that by applying the demonstration method in Class I 018 Marsawa Elementary School Sentajo Raya District can improve student mathematics learning outcomes.